The European Masters Degree in Disaster Medicine: a Decade of Exposure - Francesco eDella Corte; Ives ehubloue; Alba eRipoll Gallardo; Luca eRagazzoni; Pier Luigi eIngrassia; Michel eDebacker (Frontiers Media S.A., 2014)
Disaster medicine education has become extremely important, following the increase in mass casualty incidents, acts of terrorism and complex humanitarian emergencies. Recent studies have reported that health care professionals do not feel sufficiently knowledgeable in this area. The European Master in Disaster Medicine (EMDM) is a II level master organized by the University of Eastern Piedmont (Novara, Italy) and the Free University of Brussels (Belgium). Up to know, the EMDM has trained more than 400 students from all over the world, providing them with the appropriate competencies to coordinate medical response during crisis situations. This article provides a general overview of the Master's framework and reports its influence on graduates' professional career.